Evaluation Effects of Cefepime and Ceftriaxone on Renal Function Tests in Albino Male Rats - Jasim, Wafaa Kadhim; Ouda, Mazin H.; Umran, Rajaa (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: The most commonly used antibiotics frequently mentioned in clinical reports of drug-induced nephrotoxicity. The study is designed to investigate the in vivo effect of cefepime and ceftriaxone on functions of kidney in wistar albino rats. Materials and Methods: In this study, 18 male adult Wister albino rats were used. The animals were separated into three groups of six rats each. The rats in the first group were only given normal saline and served as the normal control group. While the rats in the other two groups were given cefepime at a dose of 90 mg/kg/day I.M. and ceftriaxone at a dose of 90 mg/kg/day I.M., respectively, and were treated as follows (for 10 days). Results: By the end of the treatment period, urine was collected by metabolic cage for total protein, pH, and specific gravity measurements. Renal function parameters were measured using blood samples. Both kidneys were removed for histopathological examination after the animals were sacrificed. The data showed no significant differences in (creatinine, BUN, uric acid, and total protein levels) between the normal, cefepime, and ceftriaxone groups, nor in urine analysis data. Histopathological images revealed an important feature of injurious lesions that are more prominent with cefepime, as well as mild inflammation to acute interstitial nephritis in ceftriaxone specimens. Conclusions: It can be concluded that cefepime has a more negative effect on renal function than ceftriaxone and that it should be used in critically ill patients.